Strategy Of Change Of Human Resources Investment By Tobacco Farm Workers In Improving Productivity - Vynysha Maretha Enjellhyna Slamet Riyadi; suswadi; Irawan, Norbertus Citra (Agribusiness Department, Agriculture Faculty, Tunas Pembangunan University, Surakarta, Indonesia, 2025)
The human resource investment focused in this study is on education and training to improve the competence and skills of farm workers. Human resource investment, especially in green education and green skills, is very important to improve the productivity of tobacco farm workers. This study aims to identify problems related to human resource (HR) investment in tobacco farm workers and formulate change strategies to improve their productivity. This study uses a mixed method, namely qualitative, quantitative, and descriptive. The results of the study showed that the results of direct observation in the field found several problems, namely: 1) Farm workers are not experts in the application of environmentally friendly technology 2) Farm workers are unable to use biopesticides 3) Farm workers are unable to choose varieties of plants that are resistant to pests 4) There is no change in the behavior of farm workers in implementing green technology . Based on these findings, this study proposes a change strategy that includes: 1) Using DBHCHT to access training environmentally friendly technology 2) Using DBHCHT to participate in biopesticide training 3) Using DBHCHT to improve experience in using varieties 4) DBHCHT is used to improve self-motivation. The implementation of this strategy is expected to improve the competence, skills, and productivity of tobacco farm workers.